Deciphering Novel Host–Herpesvirus Interactions by Virion Proteomics - Lippé, Roger (Frontiers in Microbiology, 2012)
Over the years, a vast array of information concerning the interactions of viruses with their hosts has been collected. However, recent advances in proteomics and other system biology techniques suggest these interactions are far more complex than anticipated. One particularly interesting and novel aspect is the analysis of cellular proteins incorporated into mature virions. Though sometimes considered purification contaminants in the past, their repeated detection by different laboratories suggests that a number of these proteins are bona fide viral components, some of which likely contribute to the viral life cycles. The present mini review focuses on cellular proteins detected in herpesviruses. It highlights the common cellular functions of these proteins, their potential implications for host-pathogen interactions, discusses technical limitations, the need for complementing methods and probes potential future research avenues.